Ultrastructure of Dermal Denticles in Sharpnose Shark (Rhizoprionodon lalandii) (Elasmobranchii, Carcharhinidae) - Laranjeira, M. E. [UNESP]; Guimaraes, J. P.; Amorim, A. F.; Rotundo, M.; Rici, R. E. G.; Mari, R. B. [UNESP] (Wiley-Blackwell, 2015)
The presence of denticles in the external surface, oral cavity, fins, and clasper of Elasmobranchii has been widely reported. These structures, called body denticles, may be observed on the body surface of sharks. Dermal and oral denticles are made up by a basal plate that is embedded in the dermis, forming a peduncle that grows from the base to the crown. These denticles may protect the skin against abrasion, and improve hydrodynamics and gill arches function. Rhizoprionodon lalandii is a widely distributed and very common species in Brazilian coastal areas. The aims of this study was to compare the morphology of oral and body denticles of R. lalandii to understand the implications of these structures in the behavior of these animals. Morphological analysis showed that there are differences between dermal and oral denticles, which are related to their role in different body regions. Body denticles have three cusps, and well-defined crests and ridges, and literature data suggest that suggest that hydrodynamics is their main function. Most of the oral denticles have only one cusp, and their morphology and distribution showed that their main functions are preparing food to be swallowed and protecting the oral cavity against abrasion. Microsc. Res. Tech. 78: 859-864, 2015. (C) 2015 Wiley Periodicals, Inc.
Keywords: taste papillae; lingual projection; body denticles; oral denticles; Carcharhinidae; palate